2022
DOI: 10.1177/0271678x221121841
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic performance of Mxa and transfer function analysis-based dynamic cerebral autoregulation metrics

Abstract: Dynamic cerebral autoregulation is often assessed by continuously recorded arterial blood pressure (ABP) and transcranial Doppler-derived mean cerebral blood flow velocity followed by analysis in the time and frequency domain, respectively. Sequential correlation (in the time domain, yielding e.g., the measure mean flow index, Mxa) and transfer function analysis (TFA) (in the frequency domain, yielding, e.g., normalised and non-normalised gain as well as phase in the low frequency domain) are commonly used app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Moreover, this study was limited by not having a direct measure of the dynamic cerebral autoregulation. Unfortunately, in studies run in parallel to the present study, we found the preplanned measure of cerebral autoregulation – mean flow index – to be unreliable and invalid 24–27 . Finally, as mentioned above we measured MCAv as a surrogate of global CBF.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, this study was limited by not having a direct measure of the dynamic cerebral autoregulation. Unfortunately, in studies run in parallel to the present study, we found the preplanned measure of cerebral autoregulation – mean flow index – to be unreliable and invalid 24–27 . Finally, as mentioned above we measured MCAv as a surrogate of global CBF.…”
Section: Discussionmentioning
confidence: 63%
“…Unfortunately, in studies run in parallel to the present study, we found the preplanned measure of cerebral autoregulationmean flow indexto be unreliable and invalid. [24][25][26][27] Finally, as mentioned above we measured MCAv as a surrogate of global CBF.…”
Section: Strengths/limitationsmentioning
confidence: 99%
“…Thus, in general higher values were measured ipsilateral to the injury; however, side differences were also reported in healthy volunteers (Yam et al, 2005) and patients without unilateral damage (Jochum et al, 2010;Reinhard et al, 2007). Of note, our expected behaviour is based on other methods, which are in their own way flawed or not thoroughly investigated in terms of physiolometrics (Claassen et al, 2021;Olsen, Riberholt, Plovsing et al, 2022), and furthermore do not correlate well with each other (Caldas et al, 2022;Ortega-Gutierrez et al, 2014;Pochard et al, 2020;Tzeng et al, 2012).…”
Section: Construct Validitymentioning
confidence: 67%
“…indicating that it has a limited value as a biomarker (Hartmann et al, 2023;Olsen, Riberholt, Plovsing et al, 2022).…”
Section: Bias (Units) Srd (Units) CV (%) Icc (%)mentioning
confidence: 99%
See 1 more Smart Citation